Prevention of thrombotic complications in patients in the postoperative period of total hip and knee arthroplasty: efficacy and safety - A. M. Ushanova; E. A. Okisheva; O. Iu. Mironova (Евразийский Кардиологический Журнал, 2023)
Thromboembolic complications (TEC) remain a significant problem in modern surgery, worsening the prognosis and reducing the effectiveness of the operation performed. The increase in the number of venous thromboembolisms (VTE) is determined by the severity of the initial injuries, the volume and traumatic nature of the surgical intervention, as well as the increase in the number of elderly patients with multiple comorbidities. Patients in orthopedic departments who have undergone major surgeries such as total hip arthroplasty (THA) or total knee arthroplasty (TKA) are at increased risk of VTE, leading to significant postoperative morbidity and mortality. Thromboses in extensive orthopedic surgery are caused by several prothrombotic mechanisms, such as venous injury, activation of procoagulation factors due to massive bone and tissue damage, and prolonged postoperative immobilization. The most common potential thrombotic complications after arthroplasty are deep vein thrombosis (DVT) of the lower extremities and pulmonary embolism (PE).In the absence of prophylaxis in the postoperative period of major orthopedic surgeries, TECs develop in most patients.To date, the issue of primary prevention of VTE in orthopedic patients remains relevant, and there is still no consensus on the best way to prevent thrombosis after THA and TKA.Risk assessment is the first step in preventing death and disability from VTE. Currently, mechanical and pharmacological methods are used for primary prevention in orthopedics, often in combination. Certainly, the use of antithrombotic drugs in the postoperative period is an effective way to prevent thrombosis. When prescribing antithrombotic drugs, it is also important to minimize the risk of bleeding, including in the area of postoperative wounds. Various antithrombotic drugs are used as pharmacological prophylaxis for TEC. The literature on the dosage, duration, efficacy, and safety of their use varies considerably. Our review assessed published literature on the efficacy and safety of antiplatelet agents for VTE prophylaxis.